The induction of myeloma cell death and DNA damage by tetrac, a thyroid hormone derivative. Issue 1 (January 2018) - Cohen, Keren; Abadi, Uri; Hercbergs, Aleck; Davis, Paul J; Ellis, Martin; Ashur-Fabian, Osnat
Abstract : Multiple myeloma (MM) is a plasma cell malignancy in which involvement of the thyroid hormone-integrin αvβ3 pathway was shown, and pharmacologic inhibition of this pathway is a rational approach to disease management. A thyroid hormone derivative, tetraiodothyroacetic acid (tetrac), which inhibitsl -thyroxine (T4 ) and 3, 5, 3′-triiodo-l -thyronine (T3 ) binding to αvβ3 integrin, was studied in five MM cell lines and primary bone marrow (BM) MM cells. Tetrac inhibited MM cell proliferation (absolute cell number/viability) and induced caspase-dependent apoptosis (annexin-V/PI and cell cycle). Activation of caspase-9 and caspase-3 was further demonstrated. Moreover, DNA damage markers, ataxia-telangiectasia-mutated (ATM) kinase, poly ADP-ribose polymerase (PARP-1) and histone γH2AX were induced by tetrac. The various tetrac-initiated effects were attenuated by Arg-Gly-Asp (RGD) peptide, suggesting integrin involvement. Primary BM mononuclear cells were harvested from MM patients ( n  = 39) at various disease stages. Tetrac-induced apoptosis (12/17 samples) and sensitized the cytotoxic action of bortezomib (6/9 samples). Lastly, expression of plasma membrane integrin αvβ3 was shown not only in the malignant plasma clone, but also in other cell populations within the BM samples ( n  = 25). Tetrac is anti-proliferative and pro-apoptotic in MM and cells may offer a therapeutic approach for this disease.